Physicochemical Characteristics and Anticoagulant Activities of the Polysaccharides from Sea Cucumber Pattalus mollis - Zheng, Wenqi; Zhou, Lutan; Lin, Lisha; Cai, Ying; Sun, Huifang; Zhao, Longyan; Gao, Na; Yin, Ronghua; Zhao, Jinhua (Marine drugs, 2019)
Sulfated polysaccharides from sea cucumbers possess distinct chemical structure and various biological activities. Herein, three types of polysaccharides were isolated and purified from Pattalus mollis, and their structures and bioactivities were analyzed. The fucosylated glycosaminoglycan (PmFG) had a CS-like backbone composed of the repeating units of {-4-d-GlcA-β-1,3-d-GalNAc4S6S-β-1-}, and branches of a sulfated α-l-Fuc (including Fuc2S4S, Fuc3S4S and Fuc4S with a molar ratio of 2:2.5:1) linked to O-3 of each d-GlcA. The fucan sulfate (PmFS) had a backbone consisting of a repetitively linked unit {-4-l-Fuc2S-α-1-}, and interestingly, every trisaccharide unit in its backbone was branched with a sulfated α-l-Fuc (Fuc4S or Fuc3S with a molar ratio of 4:1). Apart from the sulfated polysaccharides, two neutral glycans (PmNG-1 & -2) differing in molecular weight were also obtained and their structures were similar to animal glycogen. Anticoagulant assays indicated that PmFG and PmFS possessed strong APTT prolonging and intrinsic factor Xase inhibition activities, and the sulfated α-l-Fuc branches might contribute to the anticoagulant and anti-FXase activities of both PmFG and PmFS.